Pronunciation of young childern with cochlear implants - Dobrić, Arnalda (2008)
The aim of theis study was to analyze the pronunciation development in Croatian children with cochelar implants. All subjects were under the age of seven, had been implanted at ages between two and four years, and have been included in auditory-oral therapy in SUVAG polyclinic, Zagreb. The children were presented auditorily with one- or two- syllable words. The study included acoustic analysis of vowels, affricates and fricatives as well as evaluation of children's pronunciation by speech professionals.